2018
DOI: 10.1186/s12916-018-1042-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial registration and reporting: a survey of academic organizations in the United States

Abstract: BackgroundMany clinical trials conducted by academic organizations are not published, or are not published completely. Following the US Food and Drug Administration Amendments Act of 2007, “The Final Rule” (compliance date April 18, 2017) and a National Institutes of Health policy clarified and expanded trial registration and results reporting requirements. We sought to identify policies, procedures, and resources to support trial registration and reporting at academic organizations.MethodsWe conducted an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 50 publications
(38 reference statements)
2
20
0
Order By: Relevance
“…After adequate registration with details of research objectives, inclusion/exclusion criteria, primary and secondary outcomes, sample size calculation, analysis plan, and methodological factors related with risk of bias, authors should be cautious not to misinterpret the data [51], and provide the publicly accessible trial registration number in the published article for readers in the correct manner. The academic organizations where authors are affiliated to should provide relevant policies and resources to register trials or may even penalize researchers for non-compliance [54]. Journal editors and peer reviewers subject to concern of not detecting spin completely [55] can be systematically trained and provided with proper checklists or tools [56].…”
Section: Discussionmentioning
confidence: 99%
“…After adequate registration with details of research objectives, inclusion/exclusion criteria, primary and secondary outcomes, sample size calculation, analysis plan, and methodological factors related with risk of bias, authors should be cautious not to misinterpret the data [51], and provide the publicly accessible trial registration number in the published article for readers in the correct manner. The academic organizations where authors are affiliated to should provide relevant policies and resources to register trials or may even penalize researchers for non-compliance [54]. Journal editors and peer reviewers subject to concern of not detecting spin completely [55] can be systematically trained and provided with proper checklists or tools [56].…”
Section: Discussionmentioning
confidence: 99%
“…However, existing laws and policies may not be sufficient and novel interventions may be required to increase trial registration. Many organizations in the USA do not have policies, staff, or other resources needed to ensure their trials are registered and reported in a timely fashion [ 84 ]. Twenty stakeholders have recently affirmed that prospective registration is of critical importance and that they will implement policies with monitoring systems to improve registration and reporting of results.…”
Section: Discussionmentioning
confidence: 99%
“…Protocol registration is increasingly recommended in clinical trials [ 57 ] and SRs [ 34 ], but this study showed a low protocol enrollment of 38.3% (item 5). In a previous survey, only about one-fifth of SRs in physical therapy were registered, indicating that the enrollment rate was low [ 58 ].…”
Section: Discussionmentioning
confidence: 98%